Pretpostavke ubrzanja integracije Bosne i Hercegovine u Evropsku uniju / Assumptions of Accelerated Integration of Bosnia and Herzegovina in the European Union - Pejanović, Mirko (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
After the Dayton Peace Agreement in 1995, Bosnia and Herzegovina entered the socio-historical process of peace building. Peace building takes place through the activities of democratic forces in Bosnia and Herzegovina and the institutions of the international community and the European Union, all under the Dayton Peace Agreement’s authority. In the historical context of peace building in Bosnia and Herzegovina during the post-war and post-Dayton period, the integration of Bosnia and Herzegovina into the European Union is a strategic and historical project in the first decades of the XXI century. With the signing of the Stabilization and Association Agreement between Bosnia and Herzegovina and the European Commission, the process of Bosnia and Herzegovina's integration into the European Union started in 2008 as a contractual relationship. The delay in that Agreement’s implementation lasted until 2015, when a new course of integration of Bosnia and Herzegovina into the European Union was initiated by the German-British initiative. During 2018, the European Commission accepted the answers given by the state of Bosnia and Herzegovina to the Questionnaire filled in by all countries that are in the phase of obtaining the candidate status for the European Union membership. In addition to accepting the answer to the Questionnaire, the European Commission has established an opinion with 14 priorities, in several areas of social development, which the state of Bosnia and Herzegovina must implement through reforms. Due to the parliamentary elections in 2018 and the delay in forming the government in 2019, Bosnia and Herzegovina lost two years in carrying out reforms in the EU integrative process. The question is whether it is possible to accelerate the integration of Bosnia and Herzegovina into the European Union in the period from 2020 onwards. Acceleration of Bosnia and Herzegovina's integration into the European Union appears as a condition of all conditions for stable and economically prosperous development of the state of Bosnia and Herzegovina. There are several dangers that can lead to an even greater lag in the integration of the state of Bosnia and Herzegovina into the European Union. These dangers are mostly related to the mass migration of the working-age population from Bosnia and Herzegovina to developed European countries and to the permanent conflict between the ruling victorious parties in the Parliamentary Assembly of Bosnia and Herzegovina. In addition, geopolitical relations and influences are changing in Europe and the world, especially after the migrant crisis in 2015, and the strengthening of the influence of China and Russia on the development of international relations. Within the selected topic, possible socio-historical and geopolitical assumptions for accelerating the integration of Bosnia and Herzegovina into the European Union will be elaborated. These are assumptions that arise within Bosnia and Herzegovina itself, and then assumptions that can be provided by the institutions of the European Union and finally assumptions arising from the role of the international community through the Peace Implementation Council based on the authority to implement the Dayton Peace Agreement. When it comes to the first assumption, we have in mind the realization that the majority of citizens in the past decades support the integration of Bosnia and Herzegovina into the European Union (75% of citizens). It is a recognizable basic social consensus, which could be formed in the Parliamentary Assembly of Bosnia and Herzegovina as a broad coalition of parties for a European, democratic state of Bosnia and Herzegovina. All parties with 5% or more seats in the Parliament of Bosnia and Herzegovina would participate in a broad coalition. The second assumption refers to the role of the European Union institutions for the implementation of the Dayton Peace Agreement. This role is reflected in the work of the EU Special Representative in Bosnia and Herzegovina, which can influence Bosnia and Herzegovina's parliamentary and executive bodies to have annual reform agendas leading to Bosnia and Herzegovina's membership of the European Union. The third premise is that the Peace Implementation Council, to which the High Representative of the International Community (OHR) reports, should introduce a new strategy to influence the ruling political elites to implement political reforms with full responsibility and swiftly. with the aim of integrating Bosnia and Herzegovina into the European Union.